Architectural Models Managed by Service Agreements - Marina Anshina (Современные информационные технологии и IT-образование, 2021)
Recently, there has been an increase in interest in the Enterprise Architecture. This is due to the general complication of architectural styles used in the implementation of digital transformation and the transition to the digital economy. At the same time, there is a growing need for flexibility of enterprises and, accordingly, their architecture, i.e. to styles related to Agile Architecture. After all, Agile has long gone beyond the principles of software engineering. However, in order not to lose reliability, safety, productivity and other quality parameters while ensuring flexibility, formalization of relationships between changing elements is required. This can be achieved using the Service Architecture, when individual elements provide services to each other, the implementation of which can be hidden, encapsulated. Modern technologies and approaches, and above all cloud computing, make it possible to create, develop and maintain architectural elements of different providers, which leads to the need to formalize the relationship between them. Since in the field of ITSM there is the concept of SLA, which is precisely responsible for the formalization of relations between providers of various services, it can be used in a broader sense as a basis for the formation of flexible service architectures. The use of SLA allows you to control the quality of services, which is urgently needed for modern enterprises that build their activities and interaction with customers on a service formalized basis. The use of the service model forms the basis of ISO/IEC standards for reference architectures of new technologies: cloud services, the Internet of things and big data. They introduce the concept of measurable service, which can be based on SLA. This concept is widely known in the field of IT maintenance and operation, is the basis of the IT service model - ITSM and is well suited for service quality management. The SLA-based style is a kind of flexible enterprise service architecture and has every reason to be actively used today. The article describes the principles for the formation of such SLAs that connect different architectural layers, different roles and different elements of the reference architectural model of cloud services, as well as an example of the structure of such agreements.